Team-Based Learning in the Urban Planning Classroom. (December 2020) - Boyer, Robert H. W.
Team-based learning (TBL) is a pedagogical technique that structures most lessons of a semester around work in permanent teams of five to six students. Drawing from the author's experience using TBL plus a survey administered to students in an introductory undergraduate urban planning class, this paper illustrates how TBL enacts a nonhierarchical model of knowledge production, creates natural opportunities to practice highly valued skills in the planning profession, and can be implemented in almost any classroom space during typical classroom hours, offering an alternative to the studio or practicum course that is accessible to more courses more often.